New modelling approach for the optimal sizing of an islanded microgrid considering economic and environmental challenges. (1st February 2023) - Boutros, Fouad; Doumiati, Moustapha; Olivier, Jean-Christophe; Mougharbel, Imad; Kanaan, Hadi
Abstract: The goal of this study is to optimize the sizing of PV/Batteries/Diesel generator/Electrical load Microgrid (MG) through targeting the minimization of cost and CO2 life cycle emissions of all the MG components. In order to reach these objectives, an Energy Management System (EMS) is designed. A Mixed Integer Linear Programming (MILP) generates the power flow distribution while minimizing CO2 life cycle emissions. The power flow computed by the MILP does not operate on real-time basis. The MILP algorithm takes into consideration the future usage cost of batteries and provides the EMS by ensuring that the storage system returns back to initial conditions at the end of every representative day. An economic function computes the capital expenditure (CAPEX) and the operation expenditure (OPEX) costs using both the power flow calculated by the MILP function and the sizing parameters generated from Genetic Algorithm (GA). The GA algorithm finds a set of sizing solutions that minimize life cycle CO2 emissions and CAPEX and OPEX of the microgrid. A new modelling strategy based on hourly allocation of costs and emissions is presented in this study. It allows taking sizing decisions on hourly basis while avoiding to specify MG elements replacement time and costs. A sensitivity analysis is conducted in this paper to show the robustness of the optimal sizing towards economic and emission parameters' variation. Highlights: New approach for modelling microgrid costs and emissions. Life cycle emissions optimization using MILP. Microgrid multi-objective sizing using GA algorithm. Taking sizing decision without specifying project life time. Sizing robustness validation through a sensitivity analysis. Techno-economic analysis of the modelled microgrid.